An optimal macroprudential policy mix for segmented credit markets - Jelena Zivanovic (Bank of Canada, 2021)
This paper analyzes the design of simple macroprudential rules for bank and non-bank credit markets in a medium-scale dynamic stochastic general equilibrium model. In the model, mutual funds support corporate bond issuance by firms with access to capital markets; a banking sector supplies loans to the remaining producers. This model is used to study the optimal design of monetary and macroprudential rules and to address whether financial stability in the banking and bond markets is welfare improving. First, in response to aggregate productivity and financial shocks, the welfare-maximizing monetary policy rule implies near price stability, while the optimal macroprudential policy rule stabilizes bank credit and bond volumes. Second, there is no trade-off between price and financial stability. Third, if the central bank cannot correctly identify a sector-specific financial shock, responding optimally as if the shock affects both sectors, then welfare outcomes are negligibly worse than those under the optimal policy.
Keywords: E30; E44; E50; 330; Business fluctuations and cycles; Credit and credit aggregates; Credit risk management; Financial stability; Financial system regulation and policies